2008
DOI: 10.1007/s10897-007-9143-y
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Motivations for Pursuing Genetic Testing and their Preferences for the Provision of Genetic Services for Hearing Loss

Abstract: Genetic services for deafness are being increasingly sought due to the introduction of early hearing detection and intervention programs, as well as the rapid progress in the identification of deafness genes. This study aimed to assess the motivations of consumers for pursuing genetic testing as well as their preferences for provision of these services. We conducted 5 focus groups consisting of hearing parents of deaf children, deaf parents, and unmarried deaf adults. Motivations for pursuing genetic testing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 28 publications
4
35
2
Order By: Relevance
“…Although knowledge of genetics concepts was relatively high at baseline, there was improvement in knowledge scores after pre-test genetic counseling for participants who used ASL with an interpreter, those who used a combination of ASL and English with an interpreter, and those who used English without an interpreter. These findings suggest that pre-test genetic counseling is important for all deaf or hard-of-hearing individuals and they support provision of health services in a culturally and linguistically appropriate manner to increase deaf individuals’ genetics knowledge and comprehension (Middleton et al 2010b; Withrow et al 2008; Withrow et al 2009a). Additionally important, there was no evidence that improvement in genetics knowledge scores could be explained by idiosyncrasies of the study protocol (time between audiology and pre-test genetic counseling sessions) or personnel (genetic counselors, sign language interpreters), further supporting a conclusion that pre-test genetic counseling itself enhanced genetics knowledge outcomes of deaf or hard-of-hearing individuals.…”
Section: Discussionmentioning
confidence: 84%
“…Although knowledge of genetics concepts was relatively high at baseline, there was improvement in knowledge scores after pre-test genetic counseling for participants who used ASL with an interpreter, those who used a combination of ASL and English with an interpreter, and those who used English without an interpreter. These findings suggest that pre-test genetic counseling is important for all deaf or hard-of-hearing individuals and they support provision of health services in a culturally and linguistically appropriate manner to increase deaf individuals’ genetics knowledge and comprehension (Middleton et al 2010b; Withrow et al 2008; Withrow et al 2009a). Additionally important, there was no evidence that improvement in genetics knowledge scores could be explained by idiosyncrasies of the study protocol (time between audiology and pre-test genetic counseling sessions) or personnel (genetic counselors, sign language interpreters), further supporting a conclusion that pre-test genetic counseling itself enhanced genetics knowledge outcomes of deaf or hard-of-hearing individuals.…”
Section: Discussionmentioning
confidence: 84%
“…In the context of congenital deafness, most individuals reported that their motivation was fueled by curiosity about the etiology of their or their family member’s deafness rather than by an interest in using the information to make healthcare or reproductive decisions (Boudreault et al, 2010; Withrow, Burton, Arnos, Kalfoglou & Pandya, 2008). It is important to note, however, that non-syndromic deafness rarely has long-term health implications or specific treatments tailored to genetic testing results.…”
Section: Discussionmentioning
confidence: 99%
“…Boudreault et al (2010) found that most of their 256 deaf participants indicated that they pursued genetic testing out of curiosity regarding the etiology of their deafness. Similarly, Withrow, Burton, Arnos, Kalfoglou, and Pandya (2008) interviewed 44 individuals, including parents of children with deafness, both hearing and deaf, and single adults with deafness. The most common motivation cited was to discover the cause of deafness, however, other motivations included to alleviate guilt and to provide information for their family and for the future.…”
Section: Introductionmentioning
confidence: 99%
“…Benefits can include providing etiologic information, identifying (or allaying concerns about) comorbidities that may need referral for specialty care, planning for future medical and educational needs, facilitating estimations of the likelihood of recurrence, allowing families to better plan for the birth of a deaf or hard-of-hearing child, relieving the guilt that some parents may feel about having a child with hearing loss, enhancing ACMG PrACtiCe Guidelines psychological well-being, dispelling misinformation, and facilitating referral for unrelated hereditary conditions such as familial cancer. 48,[70][71][72][73][74][75][76][77][78][79] Furthermore, if mitochondrial DNA mutations associated with genetic susceptibility to aminoglycoside ototoxicity are discovered, it may be possible for relatives to avoid precipitating medications. [53][54][55] As with any genetics evaluation, clear communication between the genetics professionals and their patients is important for the provision of effective genetics services.…”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%